Meaningful work as a mediator between perceived organizational support for environment and employee eco-initiatives, psychological capital and alienation. Issue 6 (2nd July 2020) - Bhatnagar, Jyotsna; Aggarwal, Pranati
Abstract : Purpose: In this paper, the authors propose and empirically test an integrated model which investigates the relationship between POS-E (perceived organizational support for the environment) and employee outcomes, which are employee eco-initiatives (the first category of OCBE), employee psychological capital and alienation. Meaningful work as a mediator between POS-E and employee outcomes was also investigated. Design/methodology/approach: The study utilized a survey method to empirically test the hypothesized relationships on a sample of 303 respondents. For testing, Confirmatory factor analysis for the proposed and alternative models, Structural Equation Modeling (SEM) based on software AMOS, version 20.0 was used. This was to ensure validity and construct distinctiveness among the variables in the study and to evaluate the fit of the hypothesized measurement model in comparison to several alternate models. To estimate the effects of meaningful work (as a mediator) on the association between POS-E and eco-initiatives, psychological capital and alienation, the authors administered Sobel test. Findings: The present research augments the contemporary research on environmental sustainability and employee outcomes by further developing the emerging constructs of perceived organizational support of the environment (POS-E) and organized citizenship behavior toward the environment (OCBE), which is measured by eco-initiatives. The results imply that POS-E is positively associated with eco-initiatives and employee psychological capital and is negatively associated with alienation. The findings further suggest that meaningful work mediates the association between POS-E and all the outcome variables which are: employee-eco-initiatives, psychological capital and alienation. Research limitations/implications: The findings confirm the desired direction of research and accomplished the research objective of the study. As the consequences of POS-E imply immense value for all stakeholders, decision-makers must also reflect on the means of enhancing employees' understanding. Further, it is imperative, that the organization supports their environmental goals and values, and their green engagement. Practical implications: Results of the present study exhibit wide practical inferences for the managers. HR managers need to organize the passion for green behavior and work on intrinsic drivers of employee green engagement to let it sustain over a period of time. As society gradually expects increased organizational contributions towards environmental sustainability, this paper indicates that those employees who get an opportunity to act in coordination with environmental objectives will engage in eco-initiatives, exhibit higher psychological capital, and be less likely to feel alienated. The results imply that leaders should examine a diversity of probable interventions to enhance POS-E in order to gain from the initial rise in perceived meaningful work, employee eco-initiatives, increased psychological capital and reduced alienation. These interventions may lead to higher passion for sustainability and green behavior. Social implications: Further, this work supports the work of Toffel and Schendler (2013), whose study states that organizations should market their environment and climate initiatives, climate activism, such that customers and suppliers appreciate their leadership, and understands what matters. This work supports the work of Turaga et al. (2010), whose study states that for pro-environment behavior, environment passion is an intrinsic behavior which is needed (see Afsar et al., 2016). The current study enhances the need to trigger employee's sense of pro-environment passion at work place for significant results. Originality/value: This is a pioneer study, in India which confirms and extends the construct of POS-E using Social Exchange theory as an underpinning theory. We found that POS-E was linked with previously untested employee consequences, like employee eco-initiatives and psychological capital and that it was negatively associated with alienation. Our study confirmed mediator variable to be meaningful work in the relationship between POS-E and psychological capital, alienation and eco-initiatives